A preliminary study of the genus Hornstedtia (Zingiberaceae) in Thailand - Maknoi, Charun (Thai Forest Bulletin (Botany), 2014)
The taxonomy of the genus Hornstedtia Retz. in Thailand is re-evaluated. Four species are recognized, H. conica Ridl., H. minor (Blume) Valeton, H. leonurus (J.König) Retz. and H. scyphifera (J. König) Steud. All of them occur in Peninsular Thailand. Hornstedtia scyphifera and H. leonurus are widely distributed, whereas H. conica and H. minor are found near the Thai-Malaysian border in Yala and Narathiwat provinces only. A key to species and photographs of H. conica, H. leonurus and H. minor are provided.